How ready was the US vaccination infrastructure and network of immunization information systems for COVID-19 vaccination campaigns: Recommendations to strengthen the routine vaccination program and prepare for the next pandemic. Issue 5 (30th November 2022) - Shen, Angela K.; Sobczyk, Elizabeth A.; Coyle, Rebecca; Tirmal, Amber; Hannan, Claire
ABSTRACT: Coronavirus disease 2019 (COVID-19) pandemic vaccination campaigns globally have been unlike any effort in history. In the United States, the success of these efforts, in part, has hinged on the timely capture and reporting of an unprecedented amount of data from a significantly greater number of administering providers than for routine vaccinations. The pandemic response has highlighted the need to explore the status and value of vaccination data as the critical glue that connects all aspects of the upstream US vaccine development and downstream vaccination delivery system. In this review, we examine immunization information systems and the role that data and staffing play in pandemic responses. We offer three strategic recommendations—regarding funding, expanded provider enrollment, and data reporting—informed by a literature review, a survey and focus group from a convenience sample of 22 immunization jurisdictions, and the vision for enhanced data flow to improve future pandemic responses and routine vaccination.